1994
DOI: 10.1001/archsurg.1994.01420340057010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperbaric Oxygen and Growth Factors on Rabbit Ear Ischemic Ulcers

Abstract: Both PDGF-BB and TGF-beta 1 alone are more effective than HBO treatment by itself in accelerating the impaired wound healing produced by ischemia. However, the combination of HBO with either of the growth factors has a synergistic effect that totally reverses the deficit produced by ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 19 publications
7
99
1
1
Order By: Relevance
“…Advances in the understanding of neovascularization have made the process of angiogenesis and angiogenic factor expression prime targets for therapeutic manipulation in wound healing (26,37). Efforts have been made to induce or stimulate new blood vessel formation to reduce the unfavourable tissue effects caused by local ischaemia, or to enhance tissue repair (38). Gene therapy in this environment poses a particular challenge (39).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the understanding of neovascularization have made the process of angiogenesis and angiogenic factor expression prime targets for therapeutic manipulation in wound healing (26,37). Efforts have been made to induce or stimulate new blood vessel formation to reduce the unfavourable tissue effects caused by local ischaemia, or to enhance tissue repair (38). Gene therapy in this environment poses a particular challenge (39).…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally there is a benefit to hyperbaric oxygen therapy (HBO) in a clinically relevant ischemic rabbit ear ulcer model [42], particularly when given for a duration equivalent to clinical protocols [32]. In a clinical study periwound-tissue oxygen tension measured during HBO correlated directly with the improvement in wound healing of chronic wounds: during HBO treatment of patients with chronic leg wounds, the oxygen tensions of their wounds were measured and further compared to the wound healing rate.…”
Section: Impact Of Hyperoxia On Wound Healingmentioning
confidence: 99%
“…Recombinant growth factors (r-TGF-␤1, r-PDGF-BB) increase wound healing in ischemic rabbit ear ulcers by 200%, but still only 40% of normal at 7 days. If growth factors are applied together with HBO, the negative effect of ischemia on wound healing is completely reversed [42]. However, under conditions of 20 treatments with HBO (rather than five [42]), the effects of HBO are much greater, and no additional benefit is seen from the addition of growth factor (TGF-␤3) [32].…”
Section: Hbo and Recombinant Growth Factorsmentioning
confidence: 99%
“…Moreover, several animal studies have demonstrated that chronic hypoxia results in decreased granulation tissue production and delayed onset of re-epithelialization. 106,107 In 1985 Clyne et al reported that the diffusion of oxygen in lipodermatosclerotic or ulcerated gaiter area skin was lower than in the skin of subjects without significant disease. 108 Since it had also been proposed that pericapillary fibrin deposits might be a potential causative factor in limiting oxygen diffusion, thus contributing to tissue necrosis and ulceration, 15 Stacey et al conducted a critical study, which showed that such deposits preceded observable lipodermatosclerotic skin alterations and importantly tissue hypoxia.…”
mentioning
confidence: 99%